La imagen de la historia nacional peruana. Hispanistas, indigenistas y marxistas. Periodificaciones, proyectos y propuestas de la historiografía peruana del siglo XX (Dialogos, 2017)
Neste ensaio estudaremos as diversas perspectivas que se têm usado para explicar a história do Peru. Analisaremos as propostas de historiadores hispanicistas, indigenistas e marxistas, e finalizaremos com um exame das últimas tendências da historiografia nacional para observar se estamos recriando cenários similares neste novo século.Abstract. Various insights and perspectives that have been employed to explain the history of Peru are analyzed. Whereas suggestions of Hispanicist, First Nation and Marxist historians will be investigated, an analysis of the state-of-the-art trends of Peruvian Historiography will be forwarded to see whether similar scenes are being reestablished at the start of the new century.